Talking Wolves, Golden Fish, and Lion Sex: The Alterations to Gerald of Wales’s Topographia Hibernica as Evidence of Audience Disbelief? - Brewer, Keagan (Parergon, 2020)
In his Topographia Hibernica, Gerald of Wales describes many Irish wonders, including talking werewolves, animal–human hybrids, and bestiality. Version III, written c. 1189–93 (after a recitation in Oxford in 1188/9), defends the truth of these particular wonders. Gerald’s reactive revisions endorse the reality of the unnamed critic he attacks in the Expugnatio Hibernica (first written in 1189), whose objections seem to concern hexameral categories. The Oxford recitation of 1188/9 was probably where the critic raised these objections. A later critic, William de Montibus, bemoaned Gerald’s consideration of bestiality as a legitimate object of ethnological discourse.